A new broadband differential phase shifter fabricated using a novel CRLH structure - Zou, Yong-zhuo; Lin, Zhi-li; Ling, Ti; Yao, Jun; He, Sailing (Journal of Zhejiang University. A. Science, 2007)
Broadband phase shifters are mostly proposed and fabricated based on the scheme proposed by Shiffman, which uses a coupled line with far ends connected together and a uniform transmission line to give a differential phase shift. Based on the unique dispersion property of the composite right/left-handed （CRLH） metamaterial structure, a new configuration is presented in this paper for fabricating the broadband differential phase shifter, which employs a novel CRLH metamaterial structure as one of the differential phase-shift arms, instead of the conventional coupled line. The new circuit can achieve a phase shift of 90° in an operational bandwidth as broad as one octave and its phase deviations are quite small. An original design of the novel broadband phase shifter is presented, in which the artificial CRLH structure was implemented by microstrip quasi-lumped elements. Both the simulated and measured results of the 90° broadband differential phase shifter are presented.